Reaching beyond the 'worried well': pre-adoption characteristics of participants in 'Men on the Move', a community-based physical activity programme. (18th August 2018) - Kelly, Liam; Harrison, Michael; Richardson, Noel; Carroll, Paula; Robertson, Steve; Keohane, Aisling; Donohoe, Alex
Abstract: Background: Issues surrounding gender and men's health have become an increasing focus of public health globally. Unhealthy lifestyles and lower engagement in health promotion initiatives contributed to lower life expectancy and higher mortality rates among men. This study presents the pre-adoption characteristics of men who registered for 'Men on the Move'—a community-based physical activity (CBPA) programme, to ascertain whether the programme reached its intended target group, i.e. 'at-risk' adult men who did not meet physical activity (PA) guidelines and were likely to have multiple risk factors for cardiovascular disease (CVD). Methods: Multiple recruitment strategies were adopted to engage the target group and baseline data collection included a range of demographic, self-report and outcome measures. Results: The recruitment strategy succeeded in reaching the target group, with the majority ( n = 927) presenting being previously inactive (89.0%), overweight/obese (89.7%) and having multiple CVD risk factors (53.1% ≥ 2 risk factors). However, the strategy was less successful in engaging 'hard-to-reach' groups, with the majority being middle-aged, white, married/cohabiting, educated and employed. Conclusions: A gender-sensitized, partnership and community outreach recruitment strategy can maximize the reach and recruitment of an 'at-risk' cohort for CBPA initiatives, but more targeted approaches are needed to recruit marginalized groups of men.